INTELLECTUAL CAPITAL DISCLOSURES AND AUDIT COMPONENTS IN NON-DISCRETIONARY INCOME - Saarce Elsye Hatane; Dewi Rembulan; Josua Tarigan (Universitas Mercu Buana, 2019)
This study aims to determine the relationship of Intellectual Capital Disclosures (ICD), audit committee characteristics (size, gender, education, expertise), and audit quality toward the performance of the company measured through Non-Discretionary Net Income (NDNI) and Cash Flow Operation (CFO). This study is conducted on service listed companies in the Indonesia Stock Exchange (Service Industry) from 2010 to 2016 by panel data regression method analyzed using random effect model. The results of this study indicate that components in ICD have no significant impact on firm performance. Some components in the audit committees are found to have significant positive relationship towards financial performance. The empirical results suggest that ICD serve as a tool in aiding firm performance. A corporation should practice ICD extensively to enjoy the impact on the firm performance and value. Most research studies the relationship between intellectual capital disclosures and board diversity toward firm performance individually. The interaction of intellectual capital disclosures and audit committee characteristics is analyzed and studied to see whether audit committee characteristics is a factor that can help and improve the effectiveness of firm performance. Audit quality is also being analyzed and being taken into consideration as a variable. This is the first study to find the relationship towards the firm performance using NDNI and CFO as the dependent variables